2021
DOI: 10.1177/00111287211064790
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Relationship Between Tourism and Crime Based on a Dynamic Spatial Durbin Model

Abstract: To determine the extent to which tourism development affects crime rate, this study uses a dynamic spatial Durbin model (DSDM) to examine the spatial effect of tourism on crime. Based on a panel data set of 21 cities in Sichuan Province, China, over the 2008 to 2018 period, and after controlling for the interactive effect, the results reveal that tourism exerts a significantly negative impact on crime. This implies that tourism development can reduce crime. Moreover, tourism has a negative spatial spillover ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 54 publications
0
5
0
1
Order By: Relevance
“…In general, studies can relate to: a) general issues and trends (for example, Cró et al, 2020;Kordić et al, 2019); b) the situation in the EU (for example, Gheorghe, 2020;Vakhitova et al, 2022); c) the situation in particular EU member states (for example, Choe and Lugosi, 2022;Norio, 2021;Paliska et al, 2020). One can agree with the conclusion that crime and tourism are mutually dependent (Recher and Rubil, 2020;Zhang and Xiang, 2021). However, we believe that the globality of the European tourist market shifts the focus to the general European trends in the development of the criminal situation in this area.…”
Section: Discussionmentioning
confidence: 91%
“…In general, studies can relate to: a) general issues and trends (for example, Cró et al, 2020;Kordić et al, 2019); b) the situation in the EU (for example, Gheorghe, 2020;Vakhitova et al, 2022); c) the situation in particular EU member states (for example, Choe and Lugosi, 2022;Norio, 2021;Paliska et al, 2020). One can agree with the conclusion that crime and tourism are mutually dependent (Recher and Rubil, 2020;Zhang and Xiang, 2021). However, we believe that the globality of the European tourist market shifts the focus to the general European trends in the development of the criminal situation in this area.…”
Section: Discussionmentioning
confidence: 91%
“…To a certain extent, this aggravates the contradiction between land supply and land use and raises land transfer and housing price (Liu, 2013: p33;Tsui et al, 2016). On the demand side, tourism is a comprehensive industry closely related to agriculture, manufacturing, finance, transport and retail trade (Rosalina et al, 2015;Zhang and Xiang, 2022). The growth of the tourism sector leads to an increase in the number of tourists, which in turn stimulates the development of various industries such as accommodation, food and beverage, transportation and retail.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the predominant focus of extant literature revolves around the effects of tourism development on housing price, with little attention given to the reciprocal effect. This study is a ground-breaking work to investigate the tourism-housing price nexus in China, the world's largest tourism market (Zhang and Xiang, 2022). As heterogeneous characteristics vary across cities in China, it is necessary to conduct case-by-case analyses at the city level.…”
Section: Introductionmentioning
confidence: 99%
“…The results found that tourism can create good opportunities for criminals to commit crimes against people in tourist destinations. On the contrary, other studies view that tourism dependent on criminal activity, typology of crimes, and socioeconomic factors (Bassil et al, 2019;Fourie et al, 2020;Pappa et al, 2023;Zhang & Xiang, 2022). Several authors proved that crime and terror are related to the decline in the rate of tourist arrival, tourist activities, and tourism support among the community (Akamavi et al, 2023;Awan et al, 2023;Beha, 2023;Buigut et al, 2022;Fauzel & Seetanah, 2023;Lee et al, 2018;Polyzos et al, 2023;Raifu et al, 2022;Zaida & Attiab, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%